A comprehensive review on advances in storage pest management: Current scenario and future prospects - Guru, P. N.; Mridula, D.; Dukare, Ajinath Shridhar; Ghodki, Bhupendra M.; Paschapur, Amit Umesh; Samal, Ipsita; Nikhil Raj, M.; Padala, Vinod Kumar; Rajashekhar, Mandla; Subbanna, Avupati R. N. S. (Frontiers in Sustainable Food Systems, 2022)
Modernization of the agricultural production system led to a significant increase in annual food production intended to meet the ever-growing consumer demand. In many countries, most of the food grains produced is stored for contingency and regular supply. These stored grains, in general, are directly or indirectly infested by insects, resulting in severe grain damages and storage losses, thus, causing a threat to food safety and security. Although a variety of insect management options, such as physical, mechanical, biological, and chemical methods, are available, fumigation has been practiced for decades in storage. However, opportunities for fumigation are narrowing after the phase-out of methyl bromide. Besides, safe food and health concerns paved the path for green chemistry and non-chemical management practices. This review includes the list of stored-grain insects and their detection methods. The different management strategies such as the modern storage structures (hermetic and low-pressure storages), modified or controlled storage atmosphere, application of ozone as fumigant, irradiation, and physical options are presented. Further, the details on sustainable biological options, such as semiochemicals, natural enemies, biopesticides, and entomopathogenic nematodes, are supplemented. The use of inert dusts as grain protectant and in combination with the biological entity is included. Studies on alternative fumigants', novel management options, such as molecular biology tools (RNAi and CRISPR) and nanotechnology in stored grain protection, are also highlighted. This review helps the reader to understand the overall factors affecting grain storage and the different options to manage the insects causing storage losses.